Cheap chips for next wireless frontier. - Moore, S.K.
This paper discusses the technology of silicon being coaxed to operate in the 60-GHz band, where movies can be beamed from one consumer device to another. It is also expected that this technology has much faster download capability
Keywords: Consumer device; Download capability; Millimeter-wave silicon radio; Radio transceiver chips; Silicon coax; Silicon process technology